Dysmorphic cutis laxa and polymalformative syndrome. - De Rijcke, S.; Biver, A.; Laporte, M.; Toppet, V.; Ledoux, M. (European Journal of Pediatric Dermatology, 2018)
A case of congenital generalized cutis laxa, dysmorphic type, is reported in a newborn. The skin condition was associated with a polymalformative disorder including Dandy-Walker syndrome and interventricular cardiac communication. Cutaneous histology showed the typical abnormalities of elastic fibre network. To our knowledge, this is the first case of dysmorphic cutis laxa with associated neurologic and cardiac malformations.